Development Of Efficient Estimators For Finite Population Mean Using Dual Auxiliary Variables In Two Phase Sampling - Khazan Sher; Muhammad Iqbal; Hameed Ali; Gul Karam Khan; Abdurrahman Sabir; Syed Habib Shah; Fazlullah (Kurdish Studies, 2024)
The current article aims at the development of some new enhanced estimators for the finite population mean under the scenario of two phase sampling scheme. Two families of estimators have been developed and their first order approximated expressions were derived for Bias and Mean Square Error (MSE). We also determined the situations where the new estimator families demonstrate greater performance relative to the existing estimators. The efficiency of the estimators was assessed through real and artificial data sets by comparing their MSEs and Percentage Relative Efficiencies (PRE). In the end, we concluded that the new families of estimators perform better than all the estimators analyzed in this study.